2016
DOI: 10.1111/aji.12608
|View full text |Cite
|
Sign up to set email alerts
|

Minimal immune determinants connect Zika virus, human Cytomegalovirus, and Toxoplasma gondii to microcephaly‐related human proteins

Abstract: Aiming at the molecular definition of the relationship(s) between prenatal infections and fetal microcephaly and using pentapeptides as minimal immune determinants, we analyzed the peptide matching between proteins from infectious agents involved in microcephalic syndromes (namely Zika virus, human Cytomegalovirus, and Toxoplasma gondii) and human proteins that, when altered, have been specifically associated with microcephaly. We report that an unexpected high number of epitopic pentapeptides (ie, 34) are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Recent studies have shown a close relationship between Zika virus infection and the occurrence of AIDP, but not AMAN 34. Interestingly, peptide sharing was reported among proteins of Zika virus, cytomegalovirus and the human peripheral nervous system 35 36. Axonal damage, conspicuous in four of our patients, may have occurred secondary to inflammation at the proximal nerve trunk 37.…”
Section: Discussionsupporting
confidence: 44%
“…Recent studies have shown a close relationship between Zika virus infection and the occurrence of AIDP, but not AMAN 34. Interestingly, peptide sharing was reported among proteins of Zika virus, cytomegalovirus and the human peripheral nervous system 35 36. Axonal damage, conspicuous in four of our patients, may have occurred secondary to inflammation at the proximal nerve trunk 37.…”
Section: Discussionsupporting
confidence: 44%
“…We found that the brain weight of DPP6-KO mice was significantly lower than WT at 3 and 6 months (Figure 4E , insert, n = 15–28 per age, p = 0.0001, F (2,104) = 9.866, Two-way ANOVA). Studies indicate that the DPP6 gene is associated with microcephaly and mental retardation (Liao et al, 2013 ; Lucchese and Kanduc, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Lucchese and Kanduc [40,41] suggested that the massive sharing of minimal epitopic determinants among pathogens -namely Zika virus, Epstein-Barr virus, Cytomegalovirus, Influenza virus, Campylobacter jejuni, and Mycoplasma pneumoniae, among others -and the consequent potential cross-reactivity might represent the molecular basis and mechanism by which different infections over time can irrevocably imprint the host immunological memory, thus leading to subsequent anamnestic, misled, immune responses. Said data [40,41] and the present ones add biochemical evidence in supporting the view that 'a cell, which has once produced antibody, is not only preempted to performing the same task again but does this on the slightest provocation by accepting what we may regard as not quite appropriate stimuli' [80].…”
Section: Resultsmentioning
confidence: 99%